Early cancer detection among rural and urban californians - Tahir Zanera; Summers Courtney; Bristol Rebecca; Sadler Georgia R; Blair Sarah L; Saltzstein Sidney L (BMC, 2006)
Abstract Background Since the stage of cancer detection generally predicts future mortality rates, a key cancer control strategy is to increase the proportion of cancers found in the early stage. This study compared stage of detection for members of rural and urban communities to determine whether disparities were present. Methods The California Cancer Registry (CCR), a total population based cancer registry, was used to examine the proportion of early stage presentation for patients with breast, melanoma, and colon cancer from 1988 to 2003. Cancer stage at time of detection for these cancers was compared for rural and urban areas. Results In patients with breast cancer, there were significantly more patients presenting at early stage in 2003 compared to 1988, but no difference in the percentage of patients presenting with early stage disease between rural and urban dwellers. There were no differences in incidence in early stage cancer incidence between these groups for melanoma patients, as well. In colorectal cancer in 1988, significantly more patients presented with early stage disease in the urban areas (42% vs 34%, p < 0.02). However, over time the rural patients were diagnosed with early stage disease with the same frequency in 2003 as 1988. Conclusion This analysis demonstrates that people in rural and urban areas have their breast, melanoma or colorectal cancers diagnosed at similar stages. Health care administrators may take this information into account in future strategic planning.